Hubungan Tingkat Pengetahuan Tentang Diet Diabetes Melitus Dengan Komplikasi Gagal Ginjal Kronik - Refianti - Marsinta; Yesi - Hasneli; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Renal insufficiency due to diabetes disease has subsequently been known by the name of Diabetic Kidney Disease (DKD) or Diabetic Nephropathy (ND) is a complication of diabetes that is included in microvascular complications, the complications that occur in small blood vessels (small). The purpose of this research was to determined the level of knowledge about DM dietery with complication of kidney failure. Samples of this research taken by using purposive sampling technique. This study used a” descriptive – correlation” research design with cross sectional study